Strategies of Teaching and Learning Process for Young Learners during the Pandemic - Dewi Ariani; Ni Nyoman Padmadewi; Luh Putu Artini (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
This study was conducted to investigate the strategy and activities in the teaching and learning process during the pandemic in Aura Sukma Insani Kindergarten and to investigate the teachers’ problems during the process of teaching English to Young Learners during the pandemic. This research used a descriptive qualitative method, i.e., case study. The research data are derived from observation, interview, documentation, and document analysis. The subject of this research was 3 classes (with 18-21 students each class) in B level (age 5-7). The interview is semi-structured with three teachers and a school principal as informants. The theory used in this research is the teaching and learning theory from Brown (2001). This study concluded that Aura Sukma Insani Kindergarten applied blended learning and applied both synchronous and asynchronous modes of learning during pandemics. Besides, to support the teaching and learning process, the school has a special program namely, orientation and induction programs, and reflection and follow-up program. In addition, the problems of teachers are mainly about the adaptation, emotional bonding, limited time allotment, students’ mood and focus, students’ social skill and characters, teachers’ preparation, parents’ involvement, lack of facilities and technical skill and cost. The results of this study have important implications for classroom practice as it can be used as a resource and as the foundation for more detailed information strategy of the teaching and learning process during the pandemic.